Case report: Levodopa challenge test is important in identifying dopamine-induced freezing of gait in patient with Parkinson’s disease - Xu, Shan-Shan; Zhu, Shi-Guo; Yuan, Cheng-Xiang; Zeng, Guo-Ling; Li, Xiao-Tian; Liu, Rong-Pei; Huang, Shi-Shi; Zhang, Xiong; Wang, Jian-Yong (Frontiers in Human Neuroscience, 2024)
Introduction: Freezing of gait (FOG) is a disabling and heterogeneous symptom in patients with Parkinson’s disease (PD). Among them, dopamine-induced FOG is rare and difficult to identify. The treatment of dopamine-induced FOG is complex. Case presentation: We herein presented a case of PD patient who complicated with refractory FOG. It was identified as dopamine-induced FOG during levodopa challenge test. Her symptoms were alleviated after we reduced the total equivalent dosage of levodopa. Conclusion: Our report emphasizes the importance of levodopa challenge test in identifying different types of FOG, which is very important for further adjusting treatment.